The Utilization of ICT as Pedagogical and Professional Competencies to Support the Professionalism of Chemistry Teachers - Wahyuni Rizka Dharma; Jimmi Copriady; Roza Linda (Indonesian Research Journal in Education |IRJE|, 2020)
This purpose of this study was to determine the influence of ICT utilization as pedagogical and professional competencies to support the professionalism of chemistry teachers. This study used a quantitative method through a survey approach with 157 chemistry teachers. The survey was conducted to obtain the data through questionnaires. The results indicated that the ICT utilization in the learning as pedagogical and profesional competencies significantly influenced toward the professionalism of chemistry teachers with the sig. 0,000<α = 0.05. Simultaneously, the use of ICT in the learning as a pedagogical competence and the ICT utilization in communicating and developing themselves as professional competencies had a significant effect on supporting the professionalism of high school chemistry teachers that was indicated by the analysis result of the F 0,000 test probability value. It was smaller than α = 0.05. The use of ICT needs to be improved by designing various efforts in the learning process i.e.,  conducting an education and ICT training to achieve the teacher skills in utilizing the ICT to support the teacher professionalism. The chemistry teachers should utilize the ICT in learning and follow an ICT training. The local government has to fix the facility and infrastructure as well as the evaluation and regulation of the ICT utilization in school to suppert the teacher professionalism.